PERLINDUNGAN HUKUM PEKERJA DENGAN PERJANJIAN KERJA WAKTU TERTENTU BERDASAR UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Hamsar Suci Amalia; Marwah Masruroh (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Legal protection for employees is regulated by the Law No. 13 of 2003 concerning Labor. The legal protection obtained by a worker relates to the fulfilment of the rights agreed between the employees and the employer, which are laid down in the employment contract, among others; wages or remuneration or salary; time, rest, and leave of work; safety, health and well-being at work; mechanisms of termination of employment relations; and etc. An employment contract is a prerequisite for the establishment of an employment relationship and for the fulfilment of the rights of the worker. An employment contract consists of a Fixed Term Employment Agreement and An Indefinite Time Work Agreement. The discussion in this study is: Forms of legal protection of workers with Fixed Term Employment Agreement under Law No. 13 of 2003 concerning Labor. The method used is normative jurisprudence with specifications of analytical descriptive research. The data collected is secondary data obtained from library material such as books, documents, archives, literature and reports related to the subject being studied. After all the material is collected, the data is analyzed qualitatively.